Sexual practices of people living with HIV/AIDS attending school of tropical medicine, Kolkata - Pranita Taraphdar; Aparajita Dasgupta; Bibhuti Saha (Wolters Kluwer Medknow Publications, 2012)
A hospital-based, cross-sectional, observational study of People Living with HIV/AIDS (PLWHAs) attending the School of Tropical Medicine (STM), Kolkata was carried out for a period of 6 months from May 2006 to October 2006, to assess the sexual practices of PLWHAs. Past sexual practice of PLWHAs revealed that 93.4% males were polygamous, compared to 16.4% females. Of them, 45.7% males and 92.8% females reported sex with a nonregular sex partner (NRSP) in 1 year. Consistent condom use was low in both sexes. Current sexual practice showed that more than four-fifth (87.9%) of the new patients and two-thirds (68.9%) of the indoor patients were currently sexually active in 1 month recall period (P=3.79, Z=0.0000). However, consistent condom use was found only in 35.5% indoor patients and 15.5% of new patients and the difference was statistically significant.